Construct Validity of the MMPI–2–RF Triarchic Psychopathy Scales in Correctional and Collegiate Samples. Issue 4 (4th July 2017) - Kutchen, Taylor J.; Wygant, Dustin B.; Tylicki, Jessica L.; Dieter, Amy M.; Veltri, Carlo O. C.; Sellbom, Martin
ABSTRACT: This study examined the MMPI–2–RF (Ben-Porath & Tellegen, 2008/2011) Triarchic Psychopathy scales recently developed by Sellbom et al. (2016 ) in 3 separate groups of male correctional inmates and 2 college samples. Participants were administered a diverse battery of psychopathy specific measures (e.g., Psychopathy Checklist–Revised [Hare, 2003 ], Psychopathic Personality Inventory–Revised [Lilienfeld & Widows, 2005 ], Triarchic Psychopathy Measure [Patrick, 2010 ]), omnibus personality and psychopathology measures such as the Personality Assessment Inventory (Morey, 2007 ) and Personality Inventory for DSM–5 (Krueger, Derringer, Markon, Watson, & Skodol, 2012 ), and narrow-band measures that capture conceptually relevant constructs. Our results generally evidenced strong support for the convergent and discriminant validity for the MMPI–2–RF Triarchic scales. Boldness was largely associated with measures of fearless dominance, social potency, and stress immunity. Meanness showed strong relationships with measures of callousness, aggression, externalizing tendencies, and poor interpersonal functioning. Disinhibition exhibited strong associations with poor impulse control, stimulus seeking, and general externalizing proclivities. Our results provide additional construct validation to both the triarchic model and MMPI–2–RF Triarchic scales. Given the widespread use of the MMPI–2–RF in correctional and forensic settings, our results have important implications for clinical assessment in these 2 areas, where psychopathy is a highly relevant construct.